COMMON ERROR IN USE CONJUNCTION IN WRITING - Najamuddin Najamuddin (SOCIETY, 2020)
Conjunction is used to make a sentence which having the cohesion and coherence in text. The absence of the right conjunction will result in having illogical meaning, and the message. Because of the important role of conjunctions in the writing process, this study aims to reveal the students’ common errors on the use of conjunction in their writing, and investigate types of errors that occur most frequently in students’ writing. This part contains the necessary conjunction In grammar, a conjunction (abbreviated CONJ or CNJ) is a part of speech that connects words, phrases, or clauses that are called the conjuncts of the conjoining construction. The term discourse marker is mostly used for conjunctions joining sentences. This definition may overlap with that of other parts of speech, so what constitutes a “conjunction” must be defined for each language. In general, a conjunction is an invariable grammatical particle and it may or may not stand between the items in a conjunction. A knowledge of words, phrases, clauses is essential to good writing and speaking, but it doesn’t mean neglected the other part of grammar. The correction of writing and speaking is to concentrate on what we are saying rather than on how we are saying it.